Te Rito Toi in New Zealand: A Caring Response to the Pandemic - O’Connor, Peter; Estellés, Marta (Frontiers in Education, 2021)
Te Rito Toi is an online open access educational resource designed to help teachers respond to the extraordinary circumstances of the pandemic and provide all children with opportunities to engage with the arts. Central to the Te Rito Toi project was the concept of well-being, one of the United Nations Sustainable Development Goals (SGD 3). The study reported in this article delved into the perspectives of a group of New Zealand educators who used Te Rito Toi after the Covid-19 lockdown to explore the ways in which this resource helped them to engage their students in both individual and collective recovery. The analysis of the interviews revealed the following four themes: (a) building relationships and a sense of belonging; (b) enhancing communication and empathy; (c) connecting with wider social issues; and (d) contributing to community recovery.